Plasma insulin concentrations in Icelandic Horses, individual variations and effects of management practices - Rey Torres, Juan Carlos (2016)
The aim of the present study was to describe pre-exercise basal plasma insulin variation levels in a group of Icelandic horses considered to be healthy on Iceland. A second aim was to investigate possible correlations between basal plasma insulin levels and individual factors like sex, age, body weight, body condition score (BCS), height and management practices such level of training, travel time before competition, forage and concentrate consumption. Data from 201 horses were collected (4-11 years) 129 mares and 72 stallions. BCS was assessed using a 5 degree scale. A venous blood sample was taken before exercise. Plasma insulin levels were analysed in duplicates by ELISA (Mercodia AB, Sweden) and between samples variation was < 10 %. ANOVA (mixed model) was used and effects considered significant at P < 0.05. Plasma insulin levels ranged from 0.01 to 0.60 μg/L. Concentrate allowance and BCS had a significant effect on the plasma insulin level. BCS ranged from 2.3 to 4.0 (approximately 4 to 7 on a 9-degree scale) and concentrate allowance from 0 to 4 kg. For one degree of increase in BCS, log-insulin increased with 0.45 μg/L and for every kilo of increase in the concentrate allowance, log-insulin increased with 0.26 μg/L. However, there were large variations in the insulinemic response to changes in BCS and concentrate allowance as reflected in low determination coefficients in the regression equations. Thus, this study shows that there may be other factors in addition to BCS and concentrate allowance that will determine the response in basal plasma insulin concentrations in young, fit and healthy Icelandic horses.